ANALISA PROSES BISNIS SIMPAN PINJAM PADA KSU JAYA MARUTI MENGGUNAKAN BUSINESS PROCESS IMPROVEMENT - Ni Kadek Ayu Nirwana; Ni Made Mila Rosa Desmayani; I Kadek Adiana Putra; Ni Wayan Wardani; Dewa Ayu Giovany Angga Indrya (Jurnal Manajemen dan Teknologi Informasi, 2024)
KSU Jaya Maruti is a form of all-business cooperative that runs various types of businesses, one of which is the savings and loan business. There are various problems and risks faced by KSU Jaya Maruti in carrying out the savings and loan business process. The problems that are often faced are in data management, such as the frequent occurrence of human errors when recording and unintentional changes to data, and difficulties in reconciling data at the time of closing the books and auditing. In this research, business process modeling (as-is) and (to-be) were created using Business Process Modeling Notation (BPMN) with the Business Process Improvement (BPI) method so that the KSU Jaya Maruti can be helped to face its problems. The results of this research recommendation are the modeling of ongoing business processes (as-is) and recommendations (to-be), as well as additional applications in the form of financial technology to carry out the recommended business processes. From the calculation of the distribution of questionnaires based on the results of the member questionnaire with respondents from 150 people, 76.89% of respondents stated that they agreed that the KSU Jaya Maruti implemented financial technology, and for the employee questionnaire with respondents from 18 people, 80.76% stated that they strongly agreed to implement financial technology.